The Views of Scholars of The Islamic Union of Subang And Sumedang On Contemporary Issues Of Family Law (Juridical Analysis of the Granting of Compulsory Wills for Heirs of Different Religions and its Contribution to the National Legal System) - Beni Ahmad Saebani; Syamsul Falah; Maulana Hasanudin; Brilyan Yudha Pratama (Dinasti Research, 2025)
Mandatory wills regulated in Article 209 of the Compilation of Islamic Law are only for adoptive parents and adopted children, there are no mandatory wills for heirs of different religions. However, the Supreme Court Decision stipulates the right to non-Muslim inheritance with a mandatory will, so it requires in-depth study. The purpose of this study is to analyze the thoughts of the scholars of the Subang and Sumedang Islamic Union regarding the obligatory will for the heirs of different religions. The framework of thinking in this study is (1) Grand Theory: The Theory of Maqasid Shari'ah by Muhammad al-Syathibi in his book al-Muwafaqot, which emphasizes that maqashid shari'ah is one of the important concepts in the study of Islamic law. The essence of the theory of maqashid shari'ah is to attract benefits and reject madharat; Middle ranges theory is Gustav Radbruch's theory of legal justice, certainty, and the usefulness of huku as the three legal principles. The applied theory is a progressive legal theory from Satjipto Rahardjo which states that progressive law is responsive and can contextualize the application of law with the basis of the development of human life. The research method used is descriptive analysis with a normative juridical approach. This research is classified as a type of qualitative research, therefore the type of data is related to the purpose of the research in question. The primary data source is taken from the views of the Islamic Union of Subang and Sumedang scholars about the inheritance of different religions. Data collection techniques with interviews and literature studies. The data is analyzed by collecting, classifying, and interpreting it with the content analysis method and then inferred. This study concludes: (1) The views of the scholars of the Subang and Sumedang Islamic Union regarding the share of inheritance for heirs of different religions depend on the content of the heirs' wills and the agreements of other Muslim heirs. Philosophically, the name heir is not the essential meaning of heir, but because there is a postulate of the Quran and al-Hadith that states that